2016
DOI: 10.1108/bij-08-2014-0078
|View full text |Cite
|
Sign up to set email alerts
|

Empirical assessment of the causal relationships among lean criteria using DEMATEL method

Abstract: Purpose It is difficult for anyone to implement all the lean tools simultaneously. One of the core issues is identifying critical criteria for the successful implementation of lean manufacturing (LM) and evaluating them. The purpose of this paper is to analyze the causal relationships of LM criteria in a machine tool manufacturing firm located in national capital region of India using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method. Design/methodology/approach The research paper presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Chung-Wei and Gwo-Hshiung (2009) claimed that the DEMATEL method was developed by the Science and Human Affairs program of the Battelle Memorial Institute of Geneva between 1972and 1976(Fontela and Gabus, 1976. This is a useful tool of causal analysis that helps the researchers to divide the criteria of any system into the categories of cause and effect (Sharma et al, 2016). DEMATEL method can confirm interdependence between factors.…”
Section: Introductionmentioning
confidence: 99%
“…Chung-Wei and Gwo-Hshiung (2009) claimed that the DEMATEL method was developed by the Science and Human Affairs program of the Battelle Memorial Institute of Geneva between 1972and 1976(Fontela and Gabus, 1976. This is a useful tool of causal analysis that helps the researchers to divide the criteria of any system into the categories of cause and effect (Sharma et al, 2016). DEMATEL method can confirm interdependence between factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have reported uncertainty in weight computation using hierarchical approach and fuzzy concepts (Boran et al, 2009;Sharma et al, 2016). Moreover, many researchers used ANP (Vinodh et al, 2011) or AHP (Kahraman et al, 2004) for ranking the alternatives.…”
Section: Motivation For the Studymentioning
confidence: 99%
“…If the effects of dimensions and factors in matrix T exceed the threshold value, they should be plotted with arrows in a casual diagram, also known as "the impact-relations map." By the same token, if the effect of dimensions and factors in matrix T is lower than the threshold value, they dispatch minor influence on other dimensions/factors (Yang et al, 2008;Seyed-Hosseini et al, 2006;Sharma et al, 2016). IRM in a net format at the dimension level is graphed in Figure 2.…”
Section: Dematel Analysis At the Dimensional Levelmentioning
confidence: 99%
“…"Redesigning the organization" (D 4 ), with the lowest "cause degree" (À0.738), was identified as the Results of the "centrality degree" analysis at the factor level, as shown in Table V, pointed out that the top three factors with relatively higher connections with other factors in ranking order are: "Consensus Building" within the school (C 2 ) yielded a centrality degree of 15.113, followed by school leaders' "High Performance Emphasis" (C 4 ) with a centrality degree of 14.732 and "Communication Skills" (C 9 ) with a centrality degree of 14.724. It was documented in the literature that the "cause degree" can be an alternative for prioritization of factors' impacts on the whole system under investigation (Yang et al, 2008;Seyed-Hosseini et al, 2006;Sharma et al, 2016). Based on the threshold value judgments on the total-influecne matrix as mentioned earlier, "Emotional/Behavioral Coping" (C 11 ), with the highest cause degree of 0.291, was the master dispatcher, which emanates 3 outputs within the dimension with a total of 4 factors including itself, and 13 outputs within the whole 19-factor framework.…”
Section: Dematel Analysis At the Dimensional Levelmentioning
confidence: 99%
See 1 more Smart Citation